Modeling Interjurisdictional Tax Competition in a Federal System - Eduardo Haddad; Alexandre A. Porsse; Eduardo P. Ribeiro (European Regional Science Association (ERSA), 2006)
Interjurisdictional tax competition is a controversial theme little studied in an empirical approach in spite of the great advance in the theoretical debate at last decades. This paper aims to build a bridge between such theoretical issues and the empirical tools using an interregional general equilibrium model to evaluate the welfare effects of an experimental game of tax competition between two regional governments of the Brazilian federal system. The model recognizes the horizontal and vertical fiscal linkages underlying the Brazilian federalism. The results imply in a welfare-improving Nash equilibrium, in opposition with many theoretical issues. It can be seen that the fiscal externalities of tax competition does matter for such output not only due the mobility of the regional tax base but also because the substitution effect between regional goods and international goods since tax competition reduces the domestic prices. Additionally, the constitutional rules impose a rigid mechanism of fiscal transfers from central government to regional governments and contribute to alleviate the reduction pressures on the regional public goods because the increase in central government's tax base also increase the regional government revenues. Then, interjurisdicional tax competition in the Brazilian federal system can be associated with gains in private consumption that overcome the reduction in regional public good provisions, reinforcing the welfare-improving equilibrium.
Keywords: 330